Research on Balanced Content of Magnesium Oxide in Roller Compacted Concrete - Changli Chen; Rongfei Chen; Peng Zhao; Dongsheng Yang (Advances in Materials Science and Engineering)
In order to accelerate the application of magnesium oxide (MgO) expanding admixture in roller compacted concrete (RCC), aiming at common three-grading RCC used in water conservancy and hydropower engineering, the autoclave expansion of mortar specimens and the compressive strength of the autoclaved mortar specimens were studied by means of autoclave test and compressive strength test. Results showed that the balanced MgO content in RCC, which cannot be determined by the MgO content corresponding to 0.5% autoclave expansion rate of mortar specimens or the inflection point of the curve of autoclave expansion changing with MgO content like normal concrete, should be determined by the MgO content corresponding to the inflection point of the curve that compressive strength of autoclaved mortar specimens changes with MgO content to ensure long-term safe operation of RCC dams.